2001
DOI: 10.1111/j.1945-5100.2001.tb01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure history of the St‐Robert (H5) fall

Abstract: — The compositionally typical H5 chondrite St‐Robert has an exposure age, 7.8 Ma, indistinguishable from that of the main cluster of H chondrites. Small values of the cosmogenic 22Ne/21Ne ratio in interior samples imply a pre‐atmospheric radius on the order of 40 cm. Sample depths based on tracks and the production rates of Bhattacharya et al. (1973) range from 6 to ∼40 cm and are generally larger than depths estimated from published 60Co activities, perhaps because the track production rates adopted are too h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The results of the St-Robert fireball/meteorite fall (Brown et al, 1996;Hildebrand et al, 1997) having both cosmogenic nuclide activities from recovered meteorites (which constrained the entry mass (Leya et al, 2001)) and satellite data available, yield an apparent integral luminous efficiency (Ti) of -1 0% in the silicon pass band ofthe satellite sensor for this H chondrite. This corresponds to the fraction ofthe total initial kinetic energy converted to radiation in this pass band.…”
Section: Gross Fragmentation Entry Model Of Tagish Lake and Initial Massmentioning
confidence: 99%
“…The results of the St-Robert fireball/meteorite fall (Brown et al, 1996;Hildebrand et al, 1997) having both cosmogenic nuclide activities from recovered meteorites (which constrained the entry mass (Leya et al, 2001)) and satellite data available, yield an apparent integral luminous efficiency (Ti) of -1 0% in the silicon pass band ofthe satellite sensor for this H chondrite. This corresponds to the fraction ofthe total initial kinetic energy converted to radiation in this pass band.…”
Section: Gross Fragmentation Entry Model Of Tagish Lake and Initial Massmentioning
confidence: 99%
“…The low ( 3 He/ 21 Ne) c value reflects selective loss of 3 He compared to the Ne-loss. Since about half of the 3 He is produced by beta decay of the radioactive precursor nuclide 3 H, as pointed at by Leya et al (2001b), the lowered ( 3 He/ 21 Ne) c ratio may be partly due to 3 H loss before its radioactive decay (T 1/2 = 12.33 yr). The 3 H loss has been explained by higher diffusion rates of 3 H in metal than in silicate minerals (Leya et al, 2001a).…”
Section: Cosmogenic Light Noble Gases and Cosmic-ray Exposure Agesmentioning
confidence: 99%
“…Studies by Wilson, (1994), and Leya et al (2001) have concluded that : a) it is a monomict breccia of a H5 ordinary chondrite with S2-S3 shock levels; b) it has a high porosity and a high permeability when compared to most ordinary chondrites; c) the well preserved fusion crust is -50% more permeable than a freshly cut surface; d) it was launched from deep in its parent body about 7-8 Ma ago, without undergoing further major collision, entered in orbital resonance with Jupiter and then traveled to the Earth; e) the modelled orbit is consistent with an aphelion located within the asteroid belt; and f) the pre-atmospheric mass was between 1 and 2 tons at an entry velocity of-13 km/s.…”
Section: The St-robert Chondritementioning
confidence: 99%
“…This rapid hitemperature oxidation could affect rhenium and osmium concentrations: the volatile nature of these two elements, when in oxide form, might favour a loss. Moreover, the high permeability of this crust (Leya et al 2001) might facilitate mobility of gases within it (both osmium and rhenium form volatile oxides at high fO2). Os values but are amongst the closest to the IIIAB isochron data; in fact Cr-2 is the most concordant datum (-0.5 delta unit, see Table 3).…”
Section: Fusion Crustsmentioning
confidence: 99%
See 1 more Smart Citation